INNOVATIVE APPROACH IN THE FINANCIAL SPHERE IN THE CONDITIONS OF GLOBALIZATION OF ECONOMY - R.K. Berstembayeva; Z.K. Zhanybayeva; A.T. Issayeva (Academic Journal of Physical and Chemical Sciences, 2019)
In our time, there is a financial and economic globalization, which represents the internationalization of production, capital and information at a fundamentally new qualitative level, accompanied by an adequate change in economic relations. Finance has been the most affected by the globalization process. The introduction of innovations will allow banks to optimally allocate their resources, minimize costs, improve the delivery channels of banking products to the consumer, improve the quality of the services offered and thereby increase the efficiency of banking activities, and also ensure the growth of competitiveness of the bank in the financial market. At the same time, according to the authors, the new technologies provide the degrees of freedom and choice that were not previously available to the bank’s customers - convenience (speed, control and independence).